Head-Neck Taper Corrosion in Metal-on-Polyethylene Total Hip Arthroplasty: Risk Factors, Clinical Evaluation, and Treatment of Adverse Local Tissue Reactions. Issue 22 (15th November 2020) - Fitz, David; Klemt, Christian; Chen, Wenhao; Xiong, Liang; Yeo, Ingwon; Kwon, Young-Min
Abstract : Adverse local tissue reaction (ALTR) associated with mechanically assisted crevice corrosion of metal-on-polyethylene (MoP) head-neck modular total hip arthroplasty (THA), similarly observed in the metal-on-metal bearing, is a growing concern in MoP THA patients. Given the complex pathogenesis as well as variable clinical presentation, the diagnosis can be challenging. This article focuses on providing surgeons with an evidence-based update on (1) implant, surgical, and patient risk factors associated with ALTRs; (2) clinical systematic evaluation; and (3) surgical management options for ALTRs in MoP THA patients based on the currently available evidence.